Implementation of The Tri Hita Karana Concept in Environmentally Friendly Resource Management: A Study of Solar Power Plants in Nusa Penida - Sugara Yasa, I Wayan; Sumadi, I Ketut; Sukabawa, I Wayan (International Journal of Multidisciplinary Sciences, 2025)
The increase in electricity consumption in Bali, which is still dependent on fossil energy, presents environmental sustainability challenges. This study examines the implementation of the Tri Hita Karana concept in the management of the Suana Solar Power Plant (PLTS) in Nusa Penida as an environmentally friendly energy solution based on local wisdom. With a descriptive qualitative research method through literature study and field observation, this study explores how Tri Hita Karana. which includes Parahyangan (spiritual harmony), Pawongan (social relations), and Palemahan (harmony with nature) can be integrated in energy management. The results of the study show that Suana Solar Power Plant not only contributes to reducing carbon emissions, but also strengthens the involvement of local communities through cultural preservation programs, economic empowerment, and clean energy education. This cultural values-based approach increases public acceptance of the green energy transition and creates a more sustainable resource management model. This study emphasizes that the integration of renewable energy technology with local wisdom can be an effective strategy in sustainable development, while maintaining harmony between humans, nature, and spirituality.